LA REFORMA CONSTITUCIONAL DEL REGIONALISMO ITALIANO - Antonio D’Atena (Revista d'Estudis Autonòmics i Federals, 2007)
The constitutional reform of Italian regionalism took place in the 13th legislature(1996-2001) by means of three constitutional acts. More specifically,reforms to act V spelt the end of the revisions that replaced the model forregionalism in 1947 through the establishment of a federal-type system.This decision was taken for two reasons: the widely recognised crisis of Italianregionalism and the belief that it fell short of the demands for autonomyexpressed by some of the more economically developed areas of the country.The article examines and notes the main clauses of the reform, its posterioramendments and the results that have been obtained to date. It takesa close look at the power-sharing system and the role of special and standardautonomous regions. The article ends with a detailed bibliography tolet the reader look deeper into the issues that we have summarised here.